(untitled) (Global Journal of Science Frontier Research, 2023)
The letter reviews existing literature on fundamental particle processes in fusion fission and annihilation to reconstruct the causal inference from phenomenological evidence of the fifth cosmic force The review is interlaced with the evidence obtained on the fifth cosmic force between the non-rigid bodies of black holes and white holes The causal inference and evidence assessment use the Conformal Cyclic Cosmology as a framework which is considered to be the most promising cosmological theory currently to incorporate the fifth cosmic force